Pengaruh Lama Perendaman ZPT Air Kelapa dan Pemberian Pupuk Kotoran Sapi pada Pertumbuhan Stek Jambuair Madu Deli (Syzygium Aqueum) - Aldi Hernanda Sinulingga; Desi Sri Pasca Sari Sembiring; Maimunah Siregar (Jurnal Riset Rumpun Ilmu Tanaman, 2025)
This study aims to determine the effect of the interaction between the duration of immersion of coconut water plant growth regulators and manure on the growth of guava cuttings (Syzygium aqueum). This study used a Factorial Randomized Block Design (RAK) consisting of 2 factors with 48 plots, namely: The first factor is the duration of immersion of coconut water plant growth regulators which is given the symbol 'A' which consists of 4 levels of treatment, namely A0: without immersion, A1: 3 hours, A2: 6 hours, A3: 9 hours. The second factor is manure which is given the symbol 'S' which consists of 4 levels of treatment, namely S0: 0 g / polybag, S1: 50 g / polybag, S2: 100 g / polybag, S3: 150 g / polybag. So there are 16 combinations consisting of 3 replications. The parameters observed in this study are the age of shoot emergence, number of shoots, shoot length, leaf length, number of leaves, percentage of survival. The results of the study showed that the duration of immersion in young coconut water with growth regulators and the application of cow dung fertilizer significantly affected the growth of water apple (Syzygium aqueum) cuttings. The results showed that the duration of immersion in young coconut water with growth regulators and the application of cow dung fertilizer only significantly affected the number of shoots and leaves observed in the ninth week.